Ectoparasites may serve as vectors for the white-nose syndrome fungus. Issue 1 (December 2016) - Lučan, Radek; Bandouchova, Hana; Bartonička, Tomáš; Pikula, Jiri; Zahradníková, Alexandra; Zukal, Jan; Martínková, Natália
Abstract Background Vertebrate ectoparasites frequently play a role in transmission of infectious agents.Pseudogymnoascus destructans is a psychrophilic fungus known to cause white-nose syndrome (WNS), an emerging infectious disease of bats. It is transmitted with direct contact between bats or with contaminated environment. The aim of this study was to examine wing mites from the family Spinturnicidae parasitizing hibernating bats for the presence ofP. destructans propagules as another possible transmission route. Methods Wing mites collected from 33 bats at four hibernation sites in the Czech Republic were inspected for the presence and load of pathogen's DNA using quantitative PCR. Simultaneously, wing damage of inspected bats caused by WNS was quantified using ultraviolet light (UV) transillumination and the relationship between fungal load on wing mites and intensity of infection was subjected to correlation analysis. Results All samples of wing mites were positive for the presence of DNA ofP. destructans, indicating a high probability of their role in the transmission of the pathogen's propagules between bats. Conclusions Mechanical transport of adhesiveP. destructans spores and mycelium fragments on the body of spinturnicid mites is highly feasible. The specialised lifestyle of mites, i.e., living on bat wing membranes, the sites most typically affected by fungal growth, enables pathogen transport. Moreover, P. destructans metabolic traits suggest an ability to grow and sporulate on a range of organic substrates, including insects, which supports the possibility of growth on bat ectoparasites, at least in periods when bats roost in cold environments and enter torpor. In addition to transport of fungal propagules, mites may facilitate entry of fungal hyphae into the epidermis through injuries caused by biting.